New Perspectives on Ethnic Segregation over Time and Space: A Domains Approach - Maarten van Ham; Tiit Tammaru (Institute for the Study of Labor (IZA), 2016)
The term segregation has a strong connotation with residential neighbourhoods, and most studies investigating ethnic segregation focus on the urban mosaic of ethnic concentrations in residential neighbourhoods. However, there is now a small, but growing, literature, which focusses on segregation in other domains of daily life where inter-ethnic encounters and social interaction might take place, such as: workplaces; family/partner relationship; leisure time; education; transport, and virtual domains such as social media. The focus on residential segregation is understandable. Ethnic residential segregation is easily visible in cities as segregated neighbourhoods often have their own distinct identity and reputation. Residential segregation is also relatively easy to investigate by using register or census data on where different ethnic groups live. However, if the interest in segregation stems from the idea that we want to measure the integration of ethnic minorities in society, and from an interest in social interaction between ethnic groups, then just investigating where people live is far too limited and other domains such as workplaces should be taken into account. In this paper we present an integrated conceptual framework of ethnic segregation in different life domains in which we combine elements from the life course approach and from time geography.
Keywords: I32; J15; R23; 330; ethnic segregation; neighbourhoods; work places; life course approach; time geography; domains approach